2011
DOI: 10.1007/s10103-011-0968-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy after rapid maxillary expansion on proliferation and differentiation of osteoblastic cells

Abstract: The aim of this study was to investigate the osteoblastic activity of cells derived from the midpalatal suture upon treatment with low-level laser therapy (LLLT) after rapid maxillary expansion (RME). A total of 30 rats were divided into two groups: experimental I (15 rats with RME without LLLT) and experimental II (15 rats with RME + LLLT). The rats were euthanized at 24 h, 48 h, and 7 days after RME, when the osteoblastic cells derived from the rats' midpalatal suture were explanted. These cells were culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 27 publications
2
43
0
10
Order By: Relevance
“…Other in vitro [26][27][28] and in vivo [29][30][31] studies showed similar effects of laser irradiation on osteocalcin production.…”
Section: Discussionmentioning
confidence: 75%
“…Other in vitro [26][27][28] and in vivo [29][30][31] studies showed similar effects of laser irradiation on osteocalcin production.…”
Section: Discussionmentioning
confidence: 75%
“…A recent study demonstrated that LLLT increased the osteoblastic proliferation and gene expression of osteoblastic markers, such as alkaline phosphatase (ALP), runt-related transcription factor 2 (Runx-2), osteocalcin (OC), type I collagen (COL I), and bone sialoprotein (BSP) in osteoblasts cells derived from the midpalatal suture [19]. In addition, Wu et al, [14] used the microarray analysis to evaluate the gene expression of laser irradiated mesenquimal stem cells (MSCs) and demonstrated that various genes involved in cell proliferation, apoptosis, and the cell cycle were upregulated.…”
Section: Introductionmentioning
confidence: 99%
“…The immediate expansion of midpalatal suture was performed by inserting a stainless steel circular ring (1.5 mm thick and 0.5 mm diameter; Dental Morelli Ltda®, Sorocaba, SP, Brazil), between the maxillary incisors ( Fig. 1), as previously described (11). This appliance was kept in position with a light cured adhesive (3M® Unitek, Monrovia, CA, USA).…”
Section: Rapid Maxillary Expansion (Rme)mentioning
confidence: 99%